Consumption of Ruditapes philippinarum and Ruditapes decussatus: comparison of element accumulation and health risk - Figueira, Etelvina (2018)
Ruditapes philippinarum, a species native from the Indo-Pacific region, was introduced in Europe at the beginning of the 1970s for culture purposes, leading to a massive decrease of the native species Ruditapes decussatus and a high increase of R. philippinarum yields in Europe. Bivalves can accumulate high amounts of metals and thus easily reach concentrations that are toxic not only to themselves but also to consumers. Since differences in the accumulation of pollutants may exist between bivalve species, different health risks may be overcome. For this reason, the level of metals in seafood raises public health concerns, and international organisations like European Food Safety Authority, United States Food and Drug Administration, and Food Standards Australia and New Zealand (FSANZ) set maximum levels (MLs), above which edible seafood cannot be marketed. In order to evaluate the risk associated with the consumption of R. philippinarum and R. decussatus, both clam species were collected in the same site in Ria de Aveiro and the concentration of eight elements determined in organisms before and after a 48-h depuration period. Results evidence that even at low contaminated areas, the MLs for some elements can easily be achieved. The concentrations of As were above the reference values for FSANZ, and the provisional tolerable weekly intake (PTWI) is exceeded for As when more than 0.5 kg of R. decussatus and 0.9 kg of R. philippinarum clam flesh is consumed, in 1 week, by an adult (70 kg). When comparing with other systems worldwide, consumers of depurated clams from this coastal system have a similar or lower risk of exceeding the PTWI for Cd, As, Pb, and Hg. The recently introduced clam, R. philippinarum, accumulates lower amounts of the most health-threatening elements (less than 71 % of Cd, 40 % of As, and 20 % of Hg) than the native R. decussatus, except for Pb. R. philippinarum also reduces more the element burden when subjected to depuration than R. decussatus. Moreover, R. philippinarum allocates a lower proportion of the accumulated elements in the soluble fraction, where they are readily available. Thus, it is safer to consume R. philippinarum than R. decussatus, except when clams come from areas heavily polluted by Pb.